(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The significance of the research is found in the fact that the learner must mobilize all his abilities in order to reach the skill level required by the teacher and learner. This entails adapting all body systems to work effectively, and the researchers believe that their work in accordance with the vital rhythm can effectively help the learner reach the highest level. And the research problem is that through access to some studies on the subject of the biorhythm physical cycle, researchers have observed that a problem exists in the lack of consideration when teaching various skills in general, especially when teaching the skills of handling and suppression football in particular, and that this problem is, according to researchers, one of the factors that contribute to players’ slow growth or low level of learning. The objective of the research was to determine the impact of the physical biorhythm cycle on the development of the level of handling and suppression skills in football players. As a result, the researchers saw the study of the physical biorhythm cycle in the development of handling and suppression skills in football as advancing the level of the game and developing the skills of the players of Thi Qar Education Team. Regarding the research methodology, the researchers employed an experimental approach and devised two equivalent groups that were suitable for addressing the research problem. The research sample was deliberately selected and consisted of the players from the Thi Qar education team for the academic year (2022-2023), totaling 25 players. However, 5 players were excluded from the original sample due to their lack of homogeneity with the study variables. Consequently, the final sample size consisted of 20 players, who were randomly divided into two equal groups based on their vital rhythm. One group served as the experimental group, while the other group served as the control group, with each group comprising 10 players. The improvement of handling and suppressing skills in football through training in accordance with the experimental group’s physical biorhythm program is one of the study’s most significant findings